Implicações do processo de trabalho na saúde do triador clínico de doadores de sangue - Soares, Thais Marina (2023)
Clinical screen of blood donors is the stage where clinical and behavioral conditions of donors are evaluated with the aim of preventing damage to the health of those who donate and those who receive blood and blood products. Professionals who work in clinical screen are immersed in the relevance of blood donation, the difficulty in maintaining safe stocks and, in the conflicting situation of monotonous, repetitive work, with low technological density, in contrast, in the complexity of decision-making. This dissertation aimed to evaluate the implications of the clinical screener's work process on their health, in the context of blood banks in three states in southeastern Brazil. The method adopted was based on a quantitative approach with analysis of data collected from the socio-professional questionnaire and the adaptation of the Inventory on Work and Risk of Suffering. The research showed that the clinical screener is exposed to critical experiences of pleasure and suffering. The ‘Professional achievement’ domain demonstrates that triagists recognize the importance of their work, but the ‘Lack of recognition’ domain demonstrated that in general, clinical screeners do not have a perception of external recognition. The criteria that suggest damage to physical, social and psychological health had averages that indicate bearable activity, although some variables indicate serious levels of damage such as headaches and back pain, in addition to variables classified as critical, such as changes in sleep, pain in legs, arm pain, body pain, impatience with people in general, irritation with everything and bad mood, which need to be considered and worked on by management. The scarcity of literature on the topic and the size of the sample made it difficult to discuss the results. For this reason, future studies are suggested, including with a qualitative research method in order to expand the investigation of the risks of illness and defensive strategies for the professional category.